Analysis of digital twin and its physical object: exploring the efficiency and accuracy of datasets for real-world application - Henry Chima Ukwuoma; Gilles Dusserre; Gouenou Coatrieux; Johanne Vincent (Data Science and Management)
The concept of digital twin (DT) has recently gained popularity due to its ability to create a virtual representation of systems in order to improve the performance of its cyber-physical counterpart. This study compares and analyzes datasets of DTs and their corresponding physical objects to determine the effectiveness and dependability of DT technology for practical applications. The research aims to proffer a framework for ascertaining the level of (dis)similarity between a physical object and its DT equivalent. A study of water distribution (WADI) is put into perspective. Findings revealed that the proffered framework presents a method for ascertaining a (dis)similarity level (considering datasets) of a physical object and its DT using adequate statistical tests.